2018
DOI: 10.3390/catal8070265
|View full text |Cite
|
Sign up to set email alerts
|

A Contribution to the Experimental Microkinetic Approach of Gas/Solid Heterogeneous Catalysis: Measurement of the Individual Heats of Adsorption of Coadsorbed Species by Using the AEIR Method

Abstract: The two first surface elementary steps of a gas/solid catalytic reaction are the adsorption/desorption at least one of the reactants leading to its adsorption equilibrium which can be or not disturbed by the others surface elementary steps leading to the products. The variety of the sites of a conventional catalyst may lead to the formation of different coadsorbed species such as linear, bridged and threefold coordinated species for the adsorption of CO on supported metal particles. The aim of the present arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 93 publications
2
28
0
Order By: Relevance
“…The remarkable consistency between curves a and b with the experimental data obtained for two isobaric conditions justifies again that the AEIR may use only one isobar for the measurement of the heats of adsorption 11. Similarly to 19.5% species are slightly stronger on 19.5% TiO 2 /SiO 2 -A than 20.4% TiO 2 /SiO 2 -G consistent with the conclusions from the NH 3 adsorption.Conventional methods leading to the evolution of the differential heat of adsorption of a gas with the coverage of the surface such as microcalorimetry and isosteric method using the Clausius-Clapeyron equation provide the average heats of adsorption of coadsorbed species.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The remarkable consistency between curves a and b with the experimental data obtained for two isobaric conditions justifies again that the AEIR may use only one isobar for the measurement of the heats of adsorption 11. Similarly to 19.5% species are slightly stronger on 19.5% TiO 2 /SiO 2 -A than 20.4% TiO 2 /SiO 2 -G consistent with the conclusions from the NH 3 adsorption.Conventional methods leading to the evolution of the differential heat of adsorption of a gas with the coverage of the surface such as microcalorimetry and isosteric method using the Clausius-Clapeyron equation provide the average heats of adsorption of coadsorbed species.…”
supporting
confidence: 79%
“…The AEIR method is constituted of two main parts: (a) the identification of the adsorbed NH 3 species via their characteristic IR bands and then the study of their evolutions with an 5 increase in the adsorption temperature T a in isobaric conditions and (b) the exploitation of these IR data to obtain the individual heats of adsorption of the adsorbed species. 11 FTIR spectra of compressed disk of solid ( = 1.8 cm, m 40-80 mg) were recorded with a Nicolet 6700 spectrometer (ThermoScientific) using a small path length ( 2.2 mm) home made in-situ IR cell in transmission mode with CaF 2 windows 12 and under gas flow rates containing a partial pressure of NH 3 as described in details in the Part 1 of the series. 16 Only bands above 1250 cm -1 were observed in the present study because of the low IR transmission and then 1 h in helium (helium was dried using cold traps at 77 K) and cooled in helium to room temperature (ca 300 K) which lasted 1 h. Then the NH 3 (H 2 O) adsorption equilibrium is obtained at T a = 300 K after the switch He…”
Section: Heats Of Adsorption Of the Adsorbed Nh 3 And H 2 O Species Umentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that due to the intrinsic and/or induced heterogeneity of the adsorption sites on numerous dispersed solids the AEIR/TPAE experimental data were often consistent with the Temkin model whereas the Langmuir one was operant in few cases for weakly adsorbed species. 31 It has been shown that AEIR 31 and TPAE 32 experimental procedures maintain the adsorption equilibrium during the increase in T a which presents different advantages as compared to methods such as microcalorimetry and TPD. For instance, this prevents the contribution of mass transfer limitations which are one of the difficulties using TPD.…”
Section: Introductionmentioning
confidence: 99%
“…In the frame of microkinetic approaches for catalytic reactions, the isolation of the real intermediates among various adsorbates and the calculation of more accurate kinetic and thermodynamic parameters to refine kinetic models are still challenging. In this context, the development of new analytical tools, such as adsorption equilibrium infrared spectroscopy, provides an alternative to classical surface science studies-offering the opportunity to get more accurate heat of adsorptions of co-adsorbed species, and taking the coverage dependency into account in more realistic operating conditions [1]. In general, the extrapolation of kinetic models in very different operating conditions than those applied for its development must be taken with caution leading to unrealistic deviations and over interpretations.…”
mentioning
confidence: 99%